Perbedaan Pengetahuan Tentang Anemia, Status Gizi, Pola Menstruasi, Dan Konsumsi Tablet Tambah Darah Pada Kejadian Anemia Remaja Di RW 17 Desa Cileungsi Kecamatan Cileungsi Kabupaten Bogor - Herselowati; Nita Tri Wahyuni; Anes Patria Kumala; Al Finah Khairun Nisa (Prodi DIII Kebidanan La Tansa Mashiro, 2026)
Anemia happens when someone has a low count of red blood cells or hemoglobin. It is a significant global health concern impacting developing and developed nations. The 2017 World Health Organization (WHO) report showed that global anemia prevalence was between 40 and 88 percent. The 2012 Household Health Survey reported a 57.1 percent prevalence of anemia among 10-18 year old girls and a 39.5 percent prevalence among women of childbearing age (19-45). The 2018 Indonesian health survey (Riskesdas) reported a prevalence of 84.6 percent of iron deficiency anemia among Indonesian girls. This research was done to understand the presence of anemia in adolescents of RW 17, Cileungsi Village, Cileungsi District, Bogor Regency from differences in knowledge of anemia, nutritional status, menstrual patterns, and iron supplement consumption. The study found knowledge of anemia and presence of anemia (p = 0.000) to be significantly different, as was nutritional status (p = 0.019) and menstrual pattern (p = 0.036). The presence of anemia and iron supplement consumption was found to be significantly different (p = 0.062). From this study, it is expected that with the increase of knowledge of anemia, the behavior of adolescents will change, resulting in an improved status of nutrition and a healthy dietary pattern, as well as an increase in the consumption of iron supplements